Faktor-faktor yang mempengaruhi good governance di Kelurahan Depok Sleman Yogyakarta - Kurnia Ningsih (Jurnal Good Governance, 2017)
One important principles of good governance in public services is public participation. since good governance is a conception of a clean, democratic, and effective governmental administration, it regulate a synergistic and constructive relationship between the government, private business world and society. This research combines both quantitative and qualitative methods as mixed methods. Based on simple linear regression analysis results, it is found that technological training, participation in law and government, financial governance and assets and development of managerial values have a significant positive effect on implementation of good governance. The advice in this research is the application of technology training should be done effectively, with technological training to the employees themselves, especially in the use of computerization and internet in order to achieve tujuan that want to be achieved by trade and industry service.Keywords:good governance, technology training, participation in law and government